Optimización de la lixiviación de minerales auríferos. - Peláez Rodríguez, Henry Mario (2012)
This paper deals with the study of leaching optimization variable, in which, by increasing the oxygen concentration in the solution results are optimized. We refer to the processes known in English by the acronym PAL: Leaching Aided by Peroxide and CILO: Coal in Leaching oxygen. The material that was used for testing PAL is the mining area "Princesses" (gold and silver mine) located in the Province of Otuzco. Consists of several experimental tests PAL process, in which it is to ascertain the incidence that the use of hydrogen peroxide in the kinetics cyanidation. For which the [H2O2] present in the pulp were varied. The results obtained in the laboratory show great promise for further application, improving the results obtained in conventional processes. values of 78.8% of the total solution for the first hour of stirring using hydrogen peroxide, was obtained whereas for the test was not added this oxidizing the 27.83% of the total solution for the same period of time was obtained. In the second part of a study of CILO process, in which the increase of oxygen in the pulp is done by injecting pressurized oxygen it is presented. It is noted that this process reaches equal to those achieved in the conventional process to a much lesser time factor (4.8), which represents only 5 hours stirring recoveries. an analysis of results obtained in tests on a laboratory scale, which also have advantages for the application is done CILO.